2019
DOI: 10.1007/s13197-019-04142-5
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and sensorial evaluation of yogurt incorporated with red propolis

Abstract: The aim of the present study was to evaluate the use of red propolis extract, as a natural additive, in yogurt. For this, yogurt was produced with red propolis extract (YRP), to replace the additive chemical potassium sorbate, used in the commercial yogurt (CY). Analysis for apparent viscosity, texture and sensorial acceptance were performed. Apparent viscosity and texture measurements of the samples were similar to the control. Sensory evaluation showed that the samples of YRP reached a mean score of 9 on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
1
12
0
1
Order By: Relevance
“…The shelf life of FB10 was determined by pH, microbiological stability, LAB, and yeasts viable cell count during cold storage for 1, 7, 14, 21, and 28 days (adapted from Silva et al., 2018 and Santos et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The shelf life of FB10 was determined by pH, microbiological stability, LAB, and yeasts viable cell count during cold storage for 1, 7, 14, 21, and 28 days (adapted from Silva et al., 2018 and Santos et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…With respect to rheological properties, the addition of honey caused an increase in the viscosity values (up to 126%) [17]. In comparison, the propolis addition promoted a non-Newtonian and pseudoplastic behavior [30]. In fermented beverages, the addition of pollen also allowed a significantly high viscosity [24].…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…There is a possible explanation for the protein increase, as it has been reported that honey contains a small concentration of protein [40,41]; however, this depends on the amount of honey added as well as its quality. With respect to fat, there is some controversy over whether honey leads to an increase in fat content; because other studies maintain that adding honey to yogurt leads to a decrease in fat content [30], and that honey has a low or even no fat content [42].…”
Section: Nutritional Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Propolis is a natural heterogeneous complex matrix that is produced by honeybees by mixing resin, beeswax and other bees' own substances (Catchpole et al, 2018;Daugsch et al, 2008;Vyssotski et al, 2018). Several types of propolis were described in the literature, being characterized by their chemical diversity, geographical origin, and botanical sources (Ankovaa et al, 2000;Bankova, 2005;Gómez-Caravaca Brazil, has a distinct profile of biologic compounds, possessing flavonoids that are not detected in other types of propolis, such as biochamine A, formononetine, liquiritigenin and medicarpine (Santos et al, 2020). Other studies have also emphasized the higher concentration of isoflavonoids, pterocarpanes, chalcones, preny-lated benzophenones, terpenes and tannins in the type of propolis (Freires et al, 2016).…”
Section: Introductionmentioning
confidence: 99%